Mechanism of metamifop resistance in Digitaria ciliaris var. chrysoblephara from Jiangsu, China - Cao, Jingjing; Tao, Yuan; Zhang, Zichang; Gu, Tao; Li, Gui; Lou, Yuanlai; Wang, Hongchun (Frontiers in Plant Science, 2023)
Digitaria ciliaris var. chrysoblephara is one of the most competitive and problematic grass weeds in China. Metamifop is an aryloxyphenoxypropionate (APP) herbicide that inhibits the activity of acetyl-CoA carboxylase (ACCase) of sensitive weeds. Following the introduction of metamifop to China in 2010, it has been continuously used in rice paddy fields, thereby substantially increasing selective pressure for resistant D. ciliaris var. chrysoblephara variants. Here, populations of D. ciliaris var. chrysoblephara (JYX-8, JTX-98, and JTX-99) were observed to be highly resistant to metamifop, with resistance index (RI) values of 30.64, 14.38, and 23.19, respectively. Comparison of resistant and sensitive population ACCase gene sequences revealed that a single nucleotide substitution from TGG to TGC resulted in an amino acid substitution from tryptophan to cysteine at position 2,027 in the JYX-8 population. No corresponding substitution was observed for JTX-98 and JTX-99 populations. The ACCase cDNA of D. ciliaris var. chrysoblephara was successfully obtained by PCR and RACE methods, representing the first amplification of full length ACCase cDNA from Digitaria spp. Investigation of the relative expressions of ACCase gene revealed the lack of significant differences between sensitive and resistant populations before and after herbicide treatments. ACCase activities in resistant populations were less inhibited than in sensitive populations and recovered to the same or even higher levels compared to untreated plants. Whole-plant bioassays were also conducted to assess resistance to other ACCase inhibitors, acetolactate synthase (ALS) inhibitors, auxin mimic herbicide, and protoporphyrinogen oxidase (PPO) inhibitor. Cross-resistance and some multi-resistance were observed in the metamifop-resistant populations. This study is the first to focus on the herbicide resistance of D. ciliaris var. chrysoblephara. These results provide evidence for a target-site resistance mechanism in metamifop-resistant D. ciliaris var. chrysoblephara, while providing a better understanding of cross- and multi-resistance characteristics of resistant populations that will help in the management of herbicide-resistant D. ciliaris var. chrysoblephara.